Is There a Correlation Between Organizational Features and Digital Communication Usage? - Veselinović, Tamara S; Vlastelica Bakić, Tamara R; Cicvarić Kostić, Slavica M (Industrija, 2016)
Digitalization, networking and information sharing have brought to the paradigm shifts in both business and marketing communication. Extant scholarly and practical studies emphasize the importance of digital communication tools and activities, and explore new opportunities for organizations. Unlike previous studies, this study is not solely focused on the usage, but rather on the examination and determination of differences in the usage of digital communication in organizations of various characteristics such as size, industry, business maturity and geographical coverage. A transversal empirical study was conducted in the Republic of Serbia, on a randomly selected sample of 231 private and publicly owned organizations – companies, institutions and banks. The results indicate that the statistical difference in the usage of digital communication tools and activities by organization types exists, whereby the intensity of correlation differs depending on the organizational feature and digital communication tool or activity.
Keywords: Tool; Organization; Communication